Providing Instructional Media for Teaching Language to Young Learners - Dian Reftyawati (Jurnal Bahasa dan Sastra, 2017)
Abstract: Teaching a language for children is not an easy thing, but it is important. One important factor in learning English for children is teachers who care about the needs of their students. This study discussed the types of media prepared by teachers in language learning, especially in English. It aimed to answer the following questions: 1) How do teachers select language learning media for children? What problems do teachers face in the preparation of language learning media for children? To collect the data, the researcher employed observation and interview techniques. The results of the study showed lack of instructional media in schools and a lack of teachers’ knowledge in using various instructional media. Keywords:  instructional media, media selection, young learners Abstrak: Mengajar bahasa untuk anak-anak bukanlah hal yang mudah, tetapi merupakan hal yang penting. Salah satu faktor penting dalam belajar bahasa Inggris untuk anak-anak adalah guru yang peduli dengan kebutuhan siswa mereka. Penelitian ini membahas jenis media yang disiapkan oleh guru dalam pembelajaran bahasa, terutama dalam bahasa Inggris yang bertujuan untuk menjawab pertanyaan-pertanyaan berikut: 1) Bagaimana para guru memilih media pembelajaran bahasa untuk anak-anak? Masalah apa yang dihadapi guru dalam persiapan media pembelajaran bahasa untuk anak-anak? Untuk mengumpulkan data, peneliti menggunakan teknik observasi dan wawancara. Hasil penelitian menunjukkan kurangnya media pembelajaran di sekolah dan kurangnya pengetahuan guru dalam menggunakan berbagai media pembelajaran.           Kata-kata kunci: media pembelajaran, pemilihan media, pembelajar muda